The importance of topographic gradients in alpine permafrost modeling - Beddrich, Jonas; Gupta, Shubhangi; Wohlmuth, Barbara; Chiogna, Gabriele (Advances in Water Resources, 2022)
Alpine permafrost environments are highly vulnerable and sensitive to changes in regional and global climate trends. Thawing and degradation of permafrost has numerous adverse environmental, economic, and societal impacts. Mathematical modeling and numerical simulations provide powerful tools for predicting the degree of degradation and evolution of subsurface permafrost as a result of global warming. A particularly significant characteristic of alpine environments is the high variability in their surface geometry which drives large lateral thermal and fluid fluxes along topographic gradients. The combination of these topography-driven fluxes and unsaturated ground makes alpine systems markedly different from Arctic permafrost environments and general geotechnical ground freezing applications, and therefore, alpine permafrost demands its own specialized modeling approaches. In this work, we present a multi-physics permafrost model tailored to subsurface processes of alpine regions. In particular, we resolve the ice–water phase transitions, unsaturated conditions, and capillary actions, and account for the impact of the evolving pore space through freezing and thawing processes. Moreover, the approach is multi-dimensional, and therefore, inherently resolves the topography-driven horizontal fluxes. Through numerical case studies based on the elevation profiles of the Zugspitze (DE) and the Matterhorn (CH), we show the strong influence of lateral fluxes in 2D on active layer dynamics and the distribution of permafrost.
CRIS-Team Scopus Importer:2024-04-17
Keywords: Ice–water phase transition; Mathematical modeling; Mountain permafrost; Unsaturated flow